(3QSGdI aj JUMjM eSGFd GdLHQ HGdHQGgjf GdgfOSjIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3bGd(B: (3GdCUhd GdJi jQLY EdjgG CcKQ eSGFd GdLHQ KdGKI s
(3BNQgG (B:s
(3hPdce eG CQOfG Cf fHjf, WQjb GSJNQGLgG HGdLHQ, Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B39 - (3U(B41s
(3jdjgG JQLeI UOQ cJGH ChbdjOS dKGHJ Hf bQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B47 s
Keywords: (3GdQjGVjGJs